2010
DOI: 10.1007/s11434-010-3276-3
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal mass exponent spectrum of complex physiological time series

Abstract: Physiological signal belongs to the kind of nonstationary and time-variant ones. Thus, the nonlinear analysis methods may be better to disclose its characteristics and mechanisms. There have been plenty of evidences that physiological signal generated by complex self-regulated system may have a fractal structure. In this work, we introduce a new measure to characterize multifractality, the mass exponent spectrum curvature, which can disclose the complexity of fractal structure from total bending degree of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…They are also linearly inseparable because of their high nonlinearity and non-stationary nature [40]. They have highdimensional feature vectors because of combinations of electrodes and features.…”
Section: Statistical Analysis Of Imagined Grip Mrcpmentioning
confidence: 99%
“…They are also linearly inseparable because of their high nonlinearity and non-stationary nature [40]. They have highdimensional feature vectors because of combinations of electrodes and features.…”
Section: Statistical Analysis Of Imagined Grip Mrcpmentioning
confidence: 99%
“…Our previous studies [25] indicated that the curvature in mass exponents τ (q) is indicative of the degree of multifractality and nonlinearity. A nonlinear dependence of τ on the moments q is typical for nonlinear multifractal signals, while a linear dependence of τ on q signifies a linear fractal behavior.…”
Section: The Mass Exponent Spectrum Curvaturementioning
confidence: 99%
“…As such, the curvature of the spectrum can be used as measure of nonlinear complexity for the original time series. The estimation algorithm of the mass exponent spectrum curvature and its theoretical verifications were described [25]. In brief, according to the multi-fractal dimension theory described in Section 1.1, we produced the mass exponent τ(q) spectrum of the same ECG signal provided in Figure 1A, and the result is shown in Figure 2A.…”
Section: The Mass Exponent Spectrum Curvaturementioning
confidence: 99%
“…The correlation dimension D 2 is mainly used in chaotic time series processing and analysis. Together with the Lyapunov exponent and K-entropy, this parameter is one of the more critical characteristic parameters used to measure chaotic properties of nonlinear time sequences [1]. Based on the Phase-space Reconstruction [2][3][4] and Takens Embedding Theorem [5,6], the G-P algorithm for calculating the correlation dimension was proposed in 1983 by Grassberger and Procaccia [7,8].…”
mentioning
confidence: 99%